A Translation method analysis of Untranslatable cultural word in the Indonesan translation of Nujood Ali and Delphine Minoui's I am Nujood Age 10 and Divorced - Fauhan Khairunisa (Fak. Adab dan Ilmu Budaya UIN Sunan Kalijaga, 2022)
et,1/adil,c.1